UPAYA PENURUNAN EMISI KARBON BERBASIS MASYARAKAT DI HUTAN BERFUNGSI LINDUNG - Iis Alviya; Muhammad Zahrul Muttaqin; Mimi Salminah; Faridh Almuhayat Uhib Hamdani (Jurnal Analisis Kebijakan Kehutanan, 2018)
Protection forests have the potential to contribute to reducing emission. Management of a protection forest would be effective when local community gets involved in decision-making process. This paper aims to investigate roles of the local community in forest emission reduction program. The analysis includes community’s perception to REDD+, institutional preparedness in site level, potentials and impediments in utilising environmental services, as well as schemes for community-based REDD+. The study shows that the community’s perception to REDD+ is varied from high to moderate. The perception categorized “high” is stimulated by support from NGOs. Meanwhile, preparedness of the community to implement REDD+ has been well developed since they have developed a particular institution including a strategic plan to manage the forest. Nevertheless, the implementation has not been optimum due to complexity of institutional challenges. For instance, carbon, ecotourism and water are potential to be developed but funding has become a major handicap so that it is necessary to find an incentive scheme to support their development. Considering such condition, Plan Vivo scheme is likely to be appropriate in the Customary Forests of Rumbio and Yapase, while Verified Carbon Standard is appropriate to support the Katimpun Village Forest in developing incentive for REDD+.